House of secrets - Columbus, Chris 1958- (Balzer & Bray / HarperCollins, 2013)
Cordelia, Brendan, and Eleanor Walker, aged fifteen to eight, must rely on a mysterious book to face the Wind Witch and her father, the Storm King, who have kidnapped Dr. and Mrs. Walker and brought them to a strange world of magic
"End of book 1"...Page 490
Keywords: JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Family / General (see also headings under Social Issues); JUVENILE FICTION / Action & Adventure / General; Adventure and adventurers; Supernatural; Brothers and sisters; Books and reading; Dwellings; Fantasy; Kinderbuch